Hindy Najman. Seconding Sinai: The Development of Mosaic Discourse in Second Temple Judaism. Supplements to the Journal for the Study of Judaism 77. Leiden: Brill, 2003. xiv, 176 pp. - Jassen, Alex P. 1979- (2005)
In the present study, Hindy Najman addresses two fundamental aspects related to Second Temple Jewish literature: pseudepigrapha and the rewritten Bible. Pseudepigrapha as a literary genre signifies texts which claim as their author some privileged individual from the past. In reality, however, the attribution of authorship to some ancient figure masks the present-day composition of the text. The term rewritten Bible, in its broadest use, refers to the interpretive reworking of the scriptural text and story through such means as expansion, deletion, harmonization, and conflation. The final product retains the narrative sequence of the scriptural account though in a significantly modified form. Both of these literary techniques seemingly have at their base a manipulation and subversion of the integrity of the scriptural story and text. Pseudepigrapha asserts for a latter day author the authority and prestige of an ancient figure; rewritten Bible presents itself as a new and improved scripture.
Keywords: Rezension